Políticas públicas socioeconómicas y su incidencia en la población de la parroquia rural de Boyacá 2022-2023 - Chávez Cedeño, María Isabel (2025)
The present research aims to determine the impact of socioeconomic public policies on the quality of life of the population of the Boyacá parish, in the Chone canton. To gather information, three methods were employed: inductive, deductive, analytical, and synthetic; these allowed for the collection of data related to the research problem. In addition, field, bibliographic, and descriptive-explanatory research was conducted. Furthermore, as a field instrument, an interview was conducted with the president of the Parish GAD, which enabled direct contact with the object of study. It is worth noting that this research worked with a sample of 383 individuals from the population, to whom a survey consisting of sixteen multiple-choice items was applied. Moreover, based on the findings obtained, an improvement plan was developed, taking into account the issues identified. Finally, the data collected demonstrated that there is limited communication frequency from the Parish GAD towards the citizens, as well as low participation in accountability processes and the implementation of socioeconomic programs. In conclusion, this study highlights the importance of strengthening institutional transparency, citizen participation, and strategic planning in the management of socioeconomic public policies.